A Scoping Review on the Characteristics of Human Exposome Studies - Haddad, Nadine; Andrianou, Xanthi; Makris, Konstantinos C. (My University, 2019)
Embraced as a breaking through methodological framework, the exposome is accompanied by novel exposure assessment methods and data processing tools or models. However, systematic mapping of the landscape of exposome studies, including their characteristics, components, tools and language has not been done so far. We conducted a scoping review to answer the question: “Which main domains of the human exposome have been included in the literature and which metrics of exposure(s)/outcome(s) have been used?” We performed a comprehensive search of human studies containing the word “exposom*” and published up to March 8, 2019. We screened 1133 records and 82 studies were included in the analysis. Most studies took place in Europe. Data analysis showed the non-systematic use of the exposome term. Most studies had a longitudinal design (n = 30, 37%), were conducted on adults (n = 40, 51%), and had a clearly defined health outcome in methodology (n = 48, 61%). Omics tools, such as metabolomics were used in 38 studies (49%), while environment-wide association analysis was used in 9 studies (11%). Thirty-seven (48%) studies included all three exposome domains (general external, specific external and internal) while 33 (42%) studies included two. Despite the large number of environmental components that comprise each of the exposome domains, only a subset has been currently studied. An optimized consideration of the components from all exposome domains, as well as the standardization of the exposure and outcome assessment methods is warranted to advance the utility of the human exposome concept.
Keywords: Cohorts; Exposome; Domains; EWAS; Omics; Environmental health; Personalized medicine; Trials